2015
DOI: 10.1080/15592294.2015.1024406
|View full text |Cite
|
Sign up to set email alerts
|

HDAC inhibition attenuates cardiac hypertrophy by acetylation and deacetylation of target genes

Abstract: Pharmacological histone deacetylase (HDAC) inhibitors attenuate pathological cardiac remodeling and hypertrophic gene expression; yet, the direct histone targets remain poorly characterized. Since the inhibition of HDAC activity is associated with suppressing hypertrophy, we hypothesized histone acetylation would target genes implicated in cardiac remodeling. Trichostatin A (TSA) regulates cardiac gene expression and attenuates transverse aortic constriction (TAC) induced hypertrophy. We used chromatin immunop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 67 publications
3
80
0
1
Order By: Relevance
“…Cardiac remodeling amelioration reduces cardiac morbidity and mortality [1,23] . To prevent cardiac hypertrophy and fibrosis more effectively and to apply more efficient therapeutic intervention, it is important to explore the factors involved in ventricular growth both at the early and established stage of cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac remodeling amelioration reduces cardiac morbidity and mortality [1,23] . To prevent cardiac hypertrophy and fibrosis more effectively and to apply more efficient therapeutic intervention, it is important to explore the factors involved in ventricular growth both at the early and established stage of cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…TRAF3 was found to be epigenetically regulated in three conditions: cardiac hypertrophy (25), acute lymphoblastic leukaemia (ALL) (26) and vascular recurrence in patients treated with clopidogrel (22).…”
Section: Traf3 Epigeneticsmentioning
confidence: 99%
“…It was observed that cardiac hypertrophy was associated with increased acetylation and activation of TRAF3 and other NF-κβ target genes. HDAC inhibition was associated with an antiinflammatory effect and, therefore, with cardio-protection through histone deacetylation and inactivation of NF-κβ target genes, including TRAF3 (25).…”
Section: Traf3 Epigeneticsmentioning
confidence: 99%
See 2 more Smart Citations